Macro and micro effects of subsidy cuts: a short-run CGE analysis for Egypt - Lofgren, Hans (International Food Policy Research Institute, 1995)
Using a Computable General Equilibrium model for Egypt based on data for 1991/92, this paper analyzes the short-run impact of removing price-distorting subsidies for oil products sold domestically and for commodities covered by the consumer subsidy program. The model merges neoclassical and structuralist features. Two sets of simulations are conducted. The first involves raising the price of domestic oil products to international levels; the second simulates the impact of removing consumer subsidies. Each policy gives rise to an increase in government savings. The analysis is focused on imposing alternative macro closures in order to explore trade-offs between alternative uses for these savings: foreign debt repayment (adding to Egypt's net foreign assets), domestic investment, and government transfers to the households. The results indicate that both policies are contractionary, across all macro closures. The strongest fall in real GDP and other indicators resulted from paying back foreign debt. For the other two cases, the savings were used in a manner which simulated the domestic economy, with a trade-off between investing and improving current household conditions. On the micro level, the oil policy simulations showed a decline in domestic oil use by 6-8 percent (with an accompanying reduction in air pollution) and larger exports. For the consumer subsidy cut, the household consumption fall was relatively limited for food due to low income and price elasticities; most of the consumption cut affected other industrial goods and services. Sensitivity analysis suggested that one structuralist feature--mark-up pricing and excess capacity in much of the economy--had a strong impact on the results; when profit maximization and no excess capacity was assumed for most sectors, the changes in real GDP and other variables were much smaller.